Microsoft Excel 2013 plain & simple - Frye, Curtis, 1968- (Plain & simple., 2013)
Offers a step-by-step guide on how to navigate the latest version of Excel and explains how to build and format spreadsheets, filter and sort data, add graphics to spreadsheets, publish documents to the Web, and work with PivotTables.